Türkiye'deki yahudi toplumlarından geriye kalanlar - Bali, Rıfat N. 1948- (Libra Kitap, 2016)
The articles in this book are the stories of some of the Turkish Jewish communities that once lived in almost every province of Anatolia and Thrace. Now Jewish communities in Turkey are found only in Istanbul, in Izmir, and in Antakya. In cities like Ankara, Edirne, Adana, there are only a few people or a few families. The articles in this collection describe the lives of Jewish communities in İzmir, Mardin, Adana, Diyarbakir, Edirne, Antakya, Mersin, Van, Tokat and Istanbul, Kuzguncuk in the context of memorials. Thus, this book is bringing together the remains of memories, customs and traditions that have already remained in memory